The Protection of Indonesian Adolescent Employment Rights in Cambodia Reviewed from Indonesian Labor Law - Muhammad Firmansyah; Muhammad Faiz Al Maisi; Ari Afandi Sagala (ISNU Sumatera Utara, 2026)
The protection of the employment rights of Indonesian adolescents working abroad, especially in Cambodia, is a legal issue that needs serious attention. In practice, not a few Indonesian teenagers working in Cambodia experience violations of labor rights, such as unfair wages, excessive working hours, and working conditions that are not in accordance with humanitarian standards. This study aims to examine the protection of Indonesian adolescent employment rights in Cambodia based on the provisions of Indonesian labor law. This research uses normative legal research methods with a legislative approach and a conceptual approach. The results of the study show that laws and regulations in Indonesia, especially Law Number 13 of 2003 concerning Manpower and Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers, have provided an adequate legal basis related to the protection of the rights of workers, including adolescents. However, the implementation of this protection is still not optimal due to weak supervision, lack of coordination between agencies, and low legal understanding of workers. Therefore, it is necessary to increase supervision, strengthen cooperation between countries, and play an active role of the government in ensuring the protection of the employment rights of Indonesian adolescents abroad.